Machine Learning Models in Ecological Data Analysis: A Comparative Review - Amanov, Anuarbek; Daryn, Asan (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2026)
This article provides a comparative review of the effectiveness of machine learning models used in environmental data analysis. The aim of the study is to systematize the areas of application, advantages, limitations, and effectiveness of Linear Regression, Random Forest, Support Vector Machine, Neural Networks, and Deep Learning models in working with environmental data. Since environmental data are often multidimensional, nonlinear, spatial, and temporal, traditional statistical methods do not provide sufficient results in all cases. The results of the literature analysis prove that ensemble models such as Random Forest and XGBoost show high accuracy in many environmental forecasting tasks. While Deep Learning models are effective in analyzing complex data such as satellite imagery, biodiversity, animal movements, and time series, they require large data sets and high computational resources. In addition, the explainability of models remains an important issue. Explainable AI methods such as SHAP and LIME allow us to explain the decision-making logic of complex models. Research results show that model selection should consider explainability, data quality, computational efficiency, and ecological relevance in addition to accuracy.